Food insecurity, food assistance and weight status in US youth: new evidence from NHANES 2007–08. Issue 2 (31st January 2013) - Kohn, M. J.; Bell, J. F.; Grow, H. M. G.; Chan, G.
Summary What is already known about this subject Most prior work suggests no consistent association between food assistance programme participation and increased risk for youth overweight. Previous studies have not accounted for youth food insecurity status, which may modify this relationship. What this study adds Associations between food assistance programme participation and youth overweight are modified by food insecurity. In a national sample, food‐secure youth, but not food‐insecure youth, participating in food assistance programmes had increased body size both by body mass index and waist circumference measures. Objective To investigate food assistance participation as a risk factor for overweight and obesity in youth, and food insecurity as an effect modifier. Methods The sample included youth ages 4–17, in families ≤200% of the federal poverty line in the 2007–2008 National Health and Nutrition Examination Survey (n = 1321). Food insecurity was measured with the US Department of Agriculture survey module. Food assistance participation was assessed for Supplemental Nutrition Assistance Program, Special Supplemental Nutrition Program for Women, Infants and Children and school meals. Body size was classified by age‐ and sex‐specific body mass index (BMI) percentile, BMI z‐score and waist circumference percentile. Regression models with direct covariate adjustment and programme‐specific propensity scores, stratified by food insecurity, estimated associations between food assistance participation and body size. Results Food assistance participation was not associated with increased body size among food‐insecure youth in models with direct covariate adjustment or propensity scores. Compared with low‐income, food‐secure youth not participating in food assistance, BMI z‐scores were higher among participants in models with direct covariate adjustment (0.27–0.38 SD and 0.41–0.47 SD, for boys and girls, respectively). Using propensity scores, results were similar for boys, but less so for girls. Conclusions Food assistance programme participation is associated with increased body size in food‐secure youth, but not food‐insecure youth. Using both direct covariate adjustment and a propensity score approach, self‐selection bias may explain some, but not all, of the associations. Providing healthy food assistance that improves diet quality without contributing to excessive intake remains an important public health goal.